TRANSAKSI DAN ZAKAT CRYPTOCURRENCY: HARTA DIGITAL PERSPEKTIF HUKUM POSITIF DAN FIKIH KONTEMPORER - Permana, Harry; Irham, Muhammad Iqbal; Hamdani, Muhammad Faisal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The development of digital technology has given birth to various forms of new assets, one of which is cryptocurrency, which is popular as an investment and transaction instrument. This phenomenon raises new challenges in the Islamic legal system, especially the validity of crypto transactions and their zakat obligations. This article discusses crypto as digital assets from the perspective of positive law and contemporary fiqh from the perspective of transactions and zakat obligations. The method used is qualitative research with descriptive-comparative analysis of laws and regulations in Indonesia, as well as contemporary fiqh studies. The results of the study show that in positive law, crypto is recognized as a digital commodity that can be traded on a futures exchange, but is not yet considered a legitimate transaction tool. Meanwhile, in contemporary fiqh, scholars view crypto as assets that have exchange value and can be subject to zakat if they meet the nishab and haul requirements. This study recommends to the Government and MUI about the need for more specific regulations related to crypto zakat and education for the Muslim community so that they can manage digital assets in a sharia and legal manner.Keyword: crypto, transactions, zakat, positive law, contemporary fiqh Abstrak: Perkembangan teknologi digital telah melahirkan berbagai bentuk aset baru, salah satunya adalah cryptocurrency (mata uang kripto) yang populer sebagai instrumen investasi dan transaksi. Fenomena ini menimbulkan tantangan baru dalam sistem hukum Islam, khususnya keabsahan transaksi kripto dan kewajiban zakatnya. Artikel ini membahas kripto sebagai harta digital dalam perspektif hukum positif dan fikih kontemporer dari sisi transaksi dan kewajiban zakatnya. Metode yang digunakan adalah penelitian kualitatif dengan analisis deskriptif-komparatif terhadap peraturan perundang-undangan di Indonesia, serta kajian fikih kontemporer. Hasil kajian menunjukkan bahwa secara hukum positif, kripto diakui sebagai komoditas digital yang dapat diperdagangkan di bursa berjangka, namun belum dianggap sebagai alat transaksi yang sah. Sementara dalam fikih kontemporer, ulama memandang kripto sebagai harta yang memiliki nilai tukar dan dapat dikenakan zakat jika memenuhi syarat nishab dan haul . Penelitian ini merekomendasikan kepada Pemerintah dan MUI tentang perlunya regulasi yang lebih spesifik terkait zakat kripto serta edukasi kepada masyarakat Muslim agar dapat mengelola aset digital secara syar’i dan legal. Kata kunci: kripto, transaksi, zakat, hukum positif, fikih kontemporer